Augmented IFN-γ and TNF-α Induced by Probiotic Bacteria in NK Cells Mediate Differentiation of Stem-Like Tumors Leading to Inhibition of Tumor Growth and Reduction in Inflammatory Cytokine Release; Regulation by IL-10 - Bui, Vickie T.; Tseng, Han-Ching; Kozlowska, Anna; Maung, Phyu Ou; Kaur, Kawaljit; Topchyan, Paytsar; Jewett, Anahid (Frontiers in Immunology, 2015)
Our previous reports demonstrated that the magnitude of NK cell mediated cytotoxicity correlated directly with the stage and levels of differentiation of tumor cells. In addition, we have shown previously that activated NK cells induce growth inhibition of cancer cells through induction of differentiation resulting in the resistance of tumor cells to NK cell mediated cytotoxicity through secreted cytokines, as well as direct NK-tumor cell contact. In this report we show that in comparison to IL-2+anti-CD16mAb treated NK cells, activation of NK cells by probiotic bacteria sAJ2 in combination with IL-2 and anti-CD16mAb substantially decreases tumor growth and induces maturation, differentiation, and resistance of Oral Squamous Cancer Stem Cells (OSCSCs), Mia-Paca (MP2) stem-like/poorly differentiated pancreatic tumors, and healthy Stem Cells of Apical Papillae (SCAPs) through increased secretion of IFN-γ and TNF-α, as well as direct NK-tumor cell contact. Tumor resistance to NK cell mediated killing induced by IL-2+anti-CD16mAb+sAJ2 treated NK cells is mediated by both IFN-γ and TNF-α since antibodies to both, and not each cytokine alone, was able to restore tumor sensitivity to NK cells. Increased surface expression of CD54, B7H1, and MHC class I on NK differentiated tumors was mediated by IFN-γ since the addition of anti-IFN-γ abolished their increase and restored the ability of NK cells to trigger cytokine and chemokine release; whereas, differentiated tumors inhibited cytokine release by the NK cells. Monocytes synergized with NK cells in the presence of bacteria to induce regulated differentiation of stem cells through secretion of IL-10 resulting in resistance to NK cell mediated cytotoxicity and inhibition of cytokine release. Therefore, probiotic bacteria condition activated NK cells to provide augmented differentiation of cancer stem cells resulting in inhibition of tumor growth, increased tumor differentiation and decreased inflammatory cytokine release.